Bundling or Grouping Pavement and Bridge Projects: Analysis and Strategies. Issue 1 (2017) - Xiong, Yingge; Fricker, Jon D.; Labi, Samuel
Project grouping is a concept that aims to reduce the overall costs of projects by combining smaller-scale pavement, bridge, and other projects under a single contract. To investigate the potential for state agencies to realize the benefits of project grouping, this study looked at economies of scale and economies of competition. The study documented the decline in unit cost as the size of the project increased for numerous bridge and pavement work types. Scale economies are true for single- and multiple-project contracts. Larger contracts lend themselves to economies of scale but can discourage all but the largest firms from bidding on the work. As a result, there is a range of contract sizes (measured in this study in terms of bridge deck area or lane mile of pavement) within which the contract is neither too small nor too big. From an examination of the work types for which adequate data were available, the size of combined projects that led to the best balance between economies of scale and economies of competition were ( a ) about 20, 000 ft 2 of deck area for bridge projects and ( b ) 10 to 20 lane miles for pavement projects. The single-project and multiple-project unit cost models developed in this project can be used to screen projects for which engineers' estimates are available and identify single projects that should be considered for grouping into a multiple-project contract.